Differential Resistance Mechanisms to Glyphosate Result in Fitness Cost for Lolium perenne and L. multiflorum - Fernández-Moreno, Pablo T.; Alcántara-de la Cruz, Ricardo; Smeda, Reid J.; De Prado, Rafael (Frontiers in Plant Science, 2017)
Multiple mechanisms of resistance to glyphosate are exhibited by populations of Lolium spp. worldwide. Association of resistance with growth and reproductive fitness is an important predictor for long-term success of glyphosate-resistant (R) versus glyphosate-susceptible (S) biotypes. Numerous studies were conducted on R- and S-biotypes of Italian ryegrass (Lolium multiflorum) and perennial ryegrass (L. perenne) to characterize the underlying mechanism(s) of glyphosate resistance and associate this with growth and reproductive fitness. L. perenne expressed both altered uptake and translocation as well as a genetic change at 106-Pro to –Ser, This pattern for two resistance mechanisms is unique. L. multiflorum also exhibited altered uptake and translocation as well as duplication of EPSPS gene copies. Reduced plant biomass and height for R- versus S-biotypes of both species was evident over two growing seasons. This resulted in S- versus R- L. multiflorum producing up to 47 and 38% more seeds in 2014 and 2015, respectively. S- L. perenne produced up to 20 and 30% more seeds in 2014 and 2015, respectively. Both non-target site and target-site mechanisms of glyphosate resistance can render Lolium spp. at a competitive disadvantage. This has long-term implications for the success of glyphosate-resistant plants in the absence of selection pressure.